2016
DOI: 10.1002/ajmg.a.37593
|View full text |Cite
|
Sign up to set email alerts
|

Novel myopathy in a newborn with Shwachman–Diamond syndrome and review of neonatal presentation

Abstract: Shwachman-Diamond-Bodian syndrome (SDS) is a pleiotropic disorder in which the main features are bone marrow dysfunction and pancreatic insufficiency. Skeletal changes can occur, and in rare cases manifest as severe congenital thoracic dystrophy. We report a newborn boy with asphyxia, narrow thorax, and severe hypotonia initially suggesting a neuromuscular disease. The muscle biopsy showed myopathic changes with prominent variability in muscle fiber size and abnormal expression of developmental isoforms of myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 19 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…We hypothesized that the dysfunctional SBDS protein led to structural changes in the muscle fibers of the levator palpebrae superioris muscle, which contributed to the development of ptosis. In a case report on novel myopathy in SDS,7 muscle biopsies of the quadricep femoris showed variable hypotrophic and scattered muscle fibers with centrally located nuclei; similar findings were observed in the levator palpebrae superioris muscle biopsies of patients with congenital ptosis 8. Although these muscles are anatomically and functionally distinct, the nature of ribosomopathy may affect all skeletal muscles at a rudimentary level of protein synthesis.…”
Section: Discussionmentioning
confidence: 57%
“…We hypothesized that the dysfunctional SBDS protein led to structural changes in the muscle fibers of the levator palpebrae superioris muscle, which contributed to the development of ptosis. In a case report on novel myopathy in SDS,7 muscle biopsies of the quadricep femoris showed variable hypotrophic and scattered muscle fibers with centrally located nuclei; similar findings were observed in the levator palpebrae superioris muscle biopsies of patients with congenital ptosis 8. Although these muscles are anatomically and functionally distinct, the nature of ribosomopathy may affect all skeletal muscles at a rudimentary level of protein synthesis.…”
Section: Discussionmentioning
confidence: 57%
“…16 Topa et al reported myopathic changes in muscle biopsy of an infant with SDS who presented with neonatal thoracic dystrophy and severe hypotonia. 17 We did not perform a muscle biopsy in our patient; however, she had a less severe and transient hypotonia that improved with nutritional support. So, her hypotonia was less likely to be related with myopathic changes.…”
Section: Discussionmentioning
confidence: 83%
“…Patient No.15 presented with feeding di culty, failure to thrive and hypotonia, compound heterozygous variants of SBDS gene were identi ed and Shwachman-Diamond syndrome was diagnosed. During later follow-up, the patient gradually developed typical clinical manifestations of thrombocytopenia and neutropenia [20]. Some of our patients were incidentally found with other genetic diseases that had not yet appeared clinical symptoms, or to be carriers of recessive genetic diseases, suggesting more attention should be paid for those areas in the future.…”
Section: Genetic Manifestationsmentioning
confidence: 74%